2010
DOI: 10.5433/1679-0359.2010v31n4p1071
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de doze cultivares de milho (Zea mays L.) para silagem

Abstract: ResumoO experimento foi realizado com o objetivo de avaliar as características agronômicas e químico-bromatológica de diferentes cultivares de milho para ensilagem. Foram avaliados doze cultivares de milho em delineamento experimental em blocos casualizados, com três blocos, 12 tratamentos e três repetições. As parcelas foram constituídas por três linhas de seis metros de comprimento e espaçamento de 0,8 m entre linhas. O ciclo das plantas, do plantio à colheita, variou de 105 a 114 dias. A altura média diferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 8 publications
5
6
1
10
Order By: Relevance
“…Pereira et al (2007) evaluated the nutritional quality of maize silage and found no difference for the variables mineral matter and ethereal extract. Pinto et al (2010) found for ether extract, 4.80%, which is close to the value found in this study.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Pereira et al (2007) evaluated the nutritional quality of maize silage and found no difference for the variables mineral matter and ethereal extract. Pinto et al (2010) found for ether extract, 4.80%, which is close to the value found in this study.…”
Section: Resultssupporting
confidence: 79%
“…These values are lower than those found by Pinto et al (2010), which ranged from 49.1 to 56.2%. Gomes et al (2004) evaluated the characteristics related to maize silage productivity and observed that the correlations of NDF and degradation were negative in most cases.…”
Section: Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…De acordo com Oliveira et al (2010), essa utilização dos híbridos de milho constitui um dos fatores responsáveis pelo aumento da produtividade na cultura. No entanto, com o aumento da oferta de híbridos no mercado nacional, crescem as incertezas do agricultor quanto à escolha correta dos híbridos (SILVA et al, 2015).…”
Section: Introductionunclassified